Frontières en mouvement (Frontem) which models of cross-border cooperation for the EU? : a comparative analysis from a Euro-Atlantic perspective - Wassenberg, Birte (Border studies, 2024)
The book collects the contributions to the Jean Monnet Network Frontem on five models of cross-border cooperation in Europe: at the Franco-German, Franco-Belgian, Danish-German and Hungarian-Romanian border and on the Isle of Ireland. A comparison to the US-Canadian border tests the applicability of these models to other areas in the world